MHC class Ib-restricted CD8 T cells differ in dependence on CD4 T cell help and CD28 costimulation over the course of mouse polyomavirus infection() - Hofstetter, Amelia R. (2012)
We recently identified a protective MHC class Ib-restricted CD8 T cell response to infection with mouse polyomavirus. These CD8 T cells recognize a peptide from aa 139–147 of the VP2 viral capsid protein bound to the nonpolymorphic H-2Q9 molecule, a member of the Qa-2 family of β(2)m-associated MHC-Ib molecules. Q9:VP2.139-specific CD8 T cells exhibit an unusual inflationary response characterized by a gradual expansion over 3 months followed by a stable maintenance phase. We previously demonstrated that Q9:VP2.139-specific CD8 T cells are dependent on Ag for expansion, but not for the long-term maintenance. Here, we tested the hypothesis that the expansion and maintenance components of the Q9:VP2.139-specific T cell response are differentially dependent on CD4 T cell help and CD28 costimulation. Depletion of CD4(+) cells and CD28/CD40L blockade impaired expansion of Q9:VP2.139-specific CD8 T cells, and intrinsic CD28 signaling was sufficient for expansion. In contrast, CD4 T cell-insufficiency, but not CD28/CD40L blockade, resulted in a decline in frequency of Q9:VP2.139-specific CD8 T cells during the maintenance phase. These results indicate that the Q9:VP2.139-specific CD8 T cell response to mouse polyomavirus infection depends on CD4 T cell help and CD28 costimulation for inflationary expansion, but only on CD4 T cell help for maintenance.